VIDEO-BASED LEARNING IN SCIENCE EDUCATION: A SYSTEMATIC LITERATURE REVIEW AND BIBLIOMETRIC ANALYSIS - Bilqist, Aulia Annisa Himmatul; Rusilowati, Ani; Ellianawati, Ellianawati (EduFisika: Jurnal Pendidikan Fisika, 2026)
The rapid development of digital technology has expanded the use of videos and vlogs as learning media across science education, particularly in Environmental Science, Physics, and Mathematics. This study aims to systematically examine global research trends, intellectual structures, and thematic developments related to learning videos and vlogs through a Systematic Literature Review (SLR) combined with bibliometric analysis. Data were collected from the Scopus database using the keywords “learning” and “video/vlog” covering publications from 2015 to 2025. Article selection followed the PRISMA protocol, resulting in 657 eligible articles for analysis. Bibliometric mapping was conducted using VOSviewer and Biblioshiny to analyze collaboration networks, keyword co-occurrence, and thematic evolution. The findings identify learning and video recording as Motor Themes with the highest centrality and density, confirming the central role of video-based media in technology-supported learning and highlighting Multimedia Learning Theory as the dominant theoretical foundation. The results also indicate an emerging shift toward participatory and contextual learning vlog approaches. Unlike previous studies focusing on instructional effectiveness, this study provides a comprehensive bibliometric synthesis revealing the global research trajectory. The analysis demonstrates limited integration of ethnoscience perspectives and analogy strategies within the dominant landscape, positioning ethnoscience-based learning vlogs as a promising direction for developing contextual and culturally responsive physics and science learning.